Effectiveness Of Acupuncture In Low Back Pain Patients At Kebun Rumput Acupuncture Clinic Cimahi - Agustina, Susana; Aditya , Stefanus (Jurnal Indonesia Sosial Sains, 2025)
Lower back pain is a common health issue that significantly affects productivity and imposes a considerable economic burden on individuals and society. This study aims to evaluate the effectiveness of acupuncture in reducing lower back pain at Kebun Rumput Acupuncture Clinic in Cimahi. A quantitative observational design was used with 20 respondents, consisting of 10 men and 10 women, all experiencing lower back pain. Pain levels were assessed using the Numerical Rating Scale (NRS) before and after six sessions of acupuncture therapy. Statistical analysis was conducted using the Wilcoxon test to determine any significant changes in pain levels. The results indicated a significant reduction in pain, with an average decrease of 5.4 points on the pain scale. The p-value of 0.000 (p < 0.05) confirmed that acupuncture significantly alleviated lower back pain. The findings suggest that acupuncture is an effective alternative therapy for managing lower back pain, contributing to improved quality of life for patients. Further promotion of acupuncture as part of Traditional Chinese Medicine (TCM) is recommended, alongside increased education and training for healthcare professionals to enhance its acceptance and scientific validation.